2024
DOI: 10.1021/acs.orglett.4c01091
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Azepinoindoles and Oxepinoindoles through Brønsted-Acid-Catalyzed Cyclization of an In Situ Generated Dihydrospiroquinoline Intermediate

Rina Mahato,
Naveen Yadav,
Chinmoy Kumar Hazra

Abstract: We have developed a straightforward and efficient synthetic protocol to produce 5,6,7,12-tetrahydrobenzo[2,3]azepino[4,5-b]indole and 7,12dihydro-6H-benzo[2,3]oxepino[4,5-b]indole derivatives under mild conditions. This annulation process involves the intramolecular cyclization of the in situ generated ketimine moiety via the formation of dihydrospiroindolequinoline, which serves as a key intermediate in the reaction pathway. Several control experiments and spectroscopic studies were performed to elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(19 reference statements)
0
0
0
Order By: Relevance
“…Besides, it was found that the addition of radical scavengers such as TEMPO and BHT into the systems had no obvious prohibiting effect on the yield, suggesting that the three-component reaction might not proceed through a radical pathway. Based on previous studies and related literature, 4,15 b ,16 a ,18,21 we propose a plausible mechanistic reaction pathway to account for the product formation (Fig. 5b).…”
Section: Resultsmentioning
confidence: 87%
“…Besides, it was found that the addition of radical scavengers such as TEMPO and BHT into the systems had no obvious prohibiting effect on the yield, suggesting that the three-component reaction might not proceed through a radical pathway. Based on previous studies and related literature, 4,15 b ,16 a ,18,21 we propose a plausible mechanistic reaction pathway to account for the product formation (Fig. 5b).…”
Section: Resultsmentioning
confidence: 87%